Underrepresentation of women in top corporate leadership in the U.S. - Palola, Olivia (My University, 2026)
Women are reaching top corporate leadership positions in the United States faster than ever. At the same time the incongruity between the gender roles and leadership behaviour is at its highest when reaching top level leadership. This thesis aims to find the reasons behind the underrepresentation of women in U. S. top corporate leadership by analysing the influence of gender prejudice on expectations of leadership and explaining the barriers causing underrepresentation of women by them. The thesis is conducted as a literature review around the main research question of how does perceived incongruity between gender stereotypes and leadership expectations help explain the underrepresentation of women in top corporate leadership in the U.S. The main research question is supported by three sub-questions circling around the topics of leadership expectations, gendered expectations, stereotypes and barriers to advancement of female leaders. The theoretical framework of this thesis is described by the role congruity theory. The key findings of this thesis suggest that the perceived incongruity between gender stereotypes and leadership expectations explains the underrepresentation of women in top corporate leadership in the U.S. by defining the bases caused by prejudice for the barriers that block the advancement of women into top leadership positions. As role congruity theory suggests the key finding of this thesis is that prejudice is behind the unfavourable judgement of women and gender discrimination. This sequence of consequences stems from the masculine nature of leadership setting the base for gender prejudice, causing incongruence with leadership behaviour and desirable behaviour of women, leading to negative attitude and evaluations toward women. Together these elements lead to the appearance of the glass ceiling, blocking the way to top corporate leadership positions by creating barriers for the advancement of women, overall contributing to the underrepresentation of women.

Naiset nousevat ylimpiin yritysten johtoasemiin Yhdysvalloissa tällä hetkellä nopeampaa kuin koskaan ennen. Samaan aikaan ristiriidat sukupuoliroolien ja johtajakäyttäytymisen välillä ovat suurimmillaan yritysten ylimmissä johtoasemissa. Tämä tutkimus pyrkii löytämään syitä naisten aliedustukseen Yhdysvaltain ylimpien yritysten johtajina analysoimalla sukupuoleen liittyvien ennakkoluulojen vaikutusta johtajaodotuksiin ja selittämällä naisten aliedustukseen johtavia esteitä tämän avulla. Tutkimus on tehty kirjallisuuskatsauksena pääasiallisen tutkimuskysymyksen ympärille. Tutkimuksen pääasiallinen tutkimuskysymys tutkii kuinka havaitut ristiriidat sukupuolistereotyyppien ja johtamisodotusten välillä auttavat selittämään naisten aliedustusta ylimmissä johtoasemissa Yhdysvalloissa. Päätutkimuskysymystä tukevat kolme alakysymystä, jotka tutkivat johtajaodotuksia, sukupuolittuneita odotuksia, stereotyyppejä ja naisjohtajien etenemisen esteitä. Tutkimuksen teoreettisena viitekehyksenä toimii roolien yhteensopivuusteoria (engl. the role congruity theory). Tutkimuksen tulokset osoittavat, että havaitut ristiriidat sukupuolistereotyyppien ja johtaja-odotusten välillä selittävät naisten aliedustusta ylimpien yritysten johdossa Yhdysvalloissa määrittelemällä ennakkoluulojen asettaman pohjan haasteille, jotka estävät naisten uran kehitystä kohti korkeimpia johtoasemia. Kuten roolien yhteensopivuusteoria ehdottaa, tutkimuksen keskeisin tulos esittää ennakkoluulojen olevan naisten epäsuotuisemman arvostelun ja sukupuolisyrjinnän takana. Tämän seuraamusten summan juuret pohjautuvat johtajuuden maskuliiniseen luonteeseen, joka rakentaa pohjan sukupuoliennakkoluuloille, joka puolestaan aiheuttaa ristiriidan johtajakäyttäytymisen piirteiden ja naisten toivottavan käyt-täytymisen välille johtaen naisiin kohdistuviin negatiivisiin asenteisiin ja arviointeihin. Yhdessä nämä elementit johtavat lasikattoilmiön (eng. the glass ceiling phenomenon) syntyyn. Lasikatto estää naisten etenemisen yritysten ylimpiin johtoasemiin luomalla sille esteitä, ja kokonaisuudessaan tämä seuraamustenketju toimii edesauttajana naisten aliedustukselle.
Keywords: gender; leadership (activity); prejudices; stereotypiat; equality (values); fi=Kansainvälinen liiketoiminta|en=International Business|; fi=Kansainvälisen liiketoiminnan kandidaattiohjelma|en=Bachelor Programme in International Business|